THE ANALYSIS OF STRATEGIES USED BY THE ENGLISH TEACHERS IN TEACHING READING COMPREHENSION - Resti Diana; Zulfariati .; Marsika Sepyanda (Universitas Mahaputra Muhammad Yamin, 2022)
Identifying the strategy of teaching used by the teachers in their teaching activities is essential in junior high school classes to achieve the better competencies in English. The main purpose of this study was to discover what strategies were used by English teachers at grade eight of Junior High School 2 Kubung Solok in teaching reading comprehension in one semester of the 2019/2020 academic year. This research was designed by the combination of qualitative and quantitative descriptive research. The primary data were obtained by using questionnaires and interviews distributed to the English teachers. The secondary data were taken from students' daily English exam results by review the document on the scores stored by the teachers. Questionnaire was used in order to know what strategies were used by English teachers in teaching reading comprehension at each meeting of the week. Interviews were used to find out what, how, and how often the teachers use/implement the certain strategies in teaching reading comprehension. The third instrument, document review was used to get the data on students' daily exam results at each the time a certain strategy was used by the teachers. Based on the results of the data analysis, it is found that there were eight strategies that have been used by the teachers during one semester in teaching reading comprehension. Among the eight strategies used by the teachers, there are four strategies that were used dominantly; they were Scaffolding, Contextual Teaching, Summarizing, and Discussion strategies. The four strategies showed the highest students’ daily test results.